(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
It is certain that the old rules of ethics related to different standards of justice, mercy, moderation and chastity will always remain legitimate and credible within the circle of human interaction with each other, but this circle does not accommodate another field that has witnessed an unparalleled growth of collective activity due to the new system of applications spread by technology and its results. Very recent results. The results of these applications cannot be included in traditional ethics, as there has been a change in the nature of human action, due to the new capabilities, which are simply related, according to Jonas, to modern technology. What it was before, especially since man was not in every era without technology, and therefore Yonas says: “My question aims to explain the difference or contrast of humanity between an advanced technology and another that dates back to earlier times.”